2019
DOI: 10.1016/j.stem.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Aging Disrupts Muscle Stem Cell Function by Impairing Matricellular WISP1 Secretion from Fibro-Adipogenic Progenitors

Abstract: Highlights d Aging alters the myogenic support of FAPs to MuSCs d Aged FAPs produce less matricellular WISP1 d FAP-derived WISP1 is required for MuSC expansion and commitment d Restoring WISP1 levels rejuvenates the myogenic potential of aged MuSCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
232
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(271 citation statements)
references
References 61 publications
12
232
0
3
Order By: Relevance
“…The remaining satellite cells become unresponsive to FGF under regenerative pressure and fail to expand or self‐renew , a defect that is exacerbated by defective fibronectin deposition in old muscles undergoing regeneration, and the consequent impairment in integrin signaling . Aging also impairs the supportive function of fibro‐adipogenic progenitors (FAPs), which fail to induce the matricellular protein Wnt1‐inducible signaling pathway protein 1 (WISP1), required for satellite cell expansion and commitment .…”
Section: How Muscle Stem Cells Agementioning
confidence: 99%
See 1 more Smart Citation
“…The remaining satellite cells become unresponsive to FGF under regenerative pressure and fail to expand or self‐renew , a defect that is exacerbated by defective fibronectin deposition in old muscles undergoing regeneration, and the consequent impairment in integrin signaling . Aging also impairs the supportive function of fibro‐adipogenic progenitors (FAPs), which fail to induce the matricellular protein Wnt1‐inducible signaling pathway protein 1 (WISP1), required for satellite cell expansion and commitment .…”
Section: How Muscle Stem Cells Agementioning
confidence: 99%
“…For example, systemic pharmacological treatments to restore basal autophagy flux preserved quiescence and muscle stem cell regenerative capacity in old muscles . Similarly, systemic delivery of oxytocin restores age‐related regenerative capacity in old muscles , promoting satellite cell activation and proliferation, while systemic delivery of WISP1 during a regenerative event improves myogenic commitment and regenerative success . Moreover, systemic delivery of exogenous α‐Klotho improves muscle stem cell bioenergetics and improves regenerative capacity in aged animals .…”
Section: Interventions For Satellite Cell Rejuvenationmentioning
confidence: 99%
“…These PDGFRα + MSCs are found in most tissues, including bone marrow, heart, kidney, muscle, nerves, liver, lung, and skin in which they play crucial roles (Carr et al, 2019; Lemos and Duffield, 2018; Lynch and Watt, 2018; Rognoni et al, 2018). Despite their required normal activity during muscle regeneration (Joe et al, 2010; Heredia et al, 2013; Mathew et al, 2011; Fiore et al, 2016; Wosczyna et al, 2019), we and others have reported dysregulated behavior of these precursor cells in models of acute and chronic muscle damage, muscular dystrophy (MD), neurodegenerative diseases, and aging (Acuña et al, 2014; Contreras et al, 2016; Contreras et al, 2019c; González et al, 2017; Kopinke et al, 2017; Madaro et al, 2018; Mahmoudi et al, 2019; Lemos et al, 2015; Lukjanenko et al, 2019; Uezumi et al, 2014a). A common outcome of the dysregulation of these cells is fibrosing disorders, which include non-malignant fibroproliferative diseases with high morbidity and mortality (Lemos and Duffield, 2018; Wynn and Ramalingam, 2012).…”
Section: Introductionmentioning
confidence: 79%
“…The mitogenic activity of different growth factors and cytokines from activated FAPs and macrophages on MuSCs has been well established, and both have been shown to stimulate MuSCs to enter the cell cycle and indelibly change the availability of metabolites in tissue. However, in aging, the cellular and molecular complexion of these cells are altered and contribute to variations in MuSC crosstalk (Lukjanenko et al, 2019).…”
Section: Discussionmentioning
confidence: 99%